A novel cell migratory zone in the developing hippocampal formation. Issue 15 (14th May 2014) - Sugiyama, Taku; Osumi, Noriko; Katsuyama, Yu
ABSTRACT The hippocampal formation (HF) is a unique structure in the mammalian brain and is subdivided into the dentate gyrus, Ammon's horn, and subiculum by their functions and connectivity in the neuronal circuit. Because behaviors of the neural stem cells, neuronal progenitors, and the differentiating neurons are complex during hippocampal morphogenesis, the differentiation of these subdivisions has not been well understood. In this study, we investigated embryonic and postnatal expression of the proteins Prox1, Math2, and Ctip2, which clearly indicate principal cells of the dentate gyrus (Prox1 positive) and Ammon's horn (Math2 and Ctip2 positive). Expression patterns of Prox1 and Math2 were consistent with previously suggested localization of migratory pathways of the dentate granule cells and hippocampal pyramidal cells. Interestingly, we found intermingling of Prox1‐expressing cells and Math2‐expressing cells in a cell migratory stream, suggesting previously unknown behaviors of differentiating cells of the HF. J. Comp. Neurol. 522:3520–3538, 2014. © 2014 Wiley Periodicals, Inc.